The Impact of Productive Waqf's Implementation to the Development of Sharia Economics in South Kalimantan - Lisda Aisyah; Muhammad Noval; Darmawati Darmawati (Al-Tijary, 2021)
Waqf is one of the sources of Nation's income that can empower the sharia economy. The Implementation of waqf cannot be separated from the supervision of the Indonesian Waqf Board. Indonesian Waqf Board supervises at the provincial level as an independent institution tasked with empowering productive waqf. In this study, the supervisory process carried out by the Indonesian Waqf Board in South Kalimantan applies the empowerment of productive waqf by the Indonesian Waqf Board of South Kalimantan to the development of the sharia economy. This study aimed to determine how to implement the empowerment model applied by the Indonesian Waqf Board to the sharia economy. This research is a descriptive study with a sociological and normative approach. Data collection techniques through observation, interviews, documentation, and triangulation with the determination of informants through purposive snowball sampling. The results showed that from these results the implementation of (1) the waqf model for building construction in building facilities and infrastructure, and (2) the waqf model for business development covering agriculture, animal husbandry, and business units. The two models are then linked to management, including investment management and productive waqf distribution management. The management of the Indonesian Waqf Board in South Kalimantan implements the empowerment of Human Resources with the supervision of nazhir based on waqf law, sharia economic system, and waqf administration or entrepreneurship. The managerial process is inseparable from the leadership factor. Through direct supervision by South Kalimantan BWI staff and the Ministry of Religion, control is carried out to oversee productive waqf assets.